Building energy index and student’s perceived performance in public university buildings - Syed Yahya, S.N.N.; Ariffin, A.R.M.; Ismail, M.A. (Springer International Publishing., 2015)
Numerous studies have shown that students’ learning experience is closely associated with the physical comfort level of their teaching and learning environment. The different strategies or allocation of air-conditioning, mechanical ventilation (ACMV) and lighting systems contribute greatly to the energy performances in the buildings. This study explores the relationship between electricity consumption of academic buildings of a public university in an urban context and its student’s perceived performance. It seeks to find the answer patterns from unsuspected subjects; whether there is a difference from a lower energy-use building then one of a higher energy-use building. To achieve the objective, the study adopts the quantitative method of assessing student’s perceived performance through questionnaire survey. The questionnaires, adopted from Building Use Studies, UK, were distributed randomly through convenience sampling to students from two academic buildings in the campus. Both buildings were selected through purposive sampling method with specific inclusion and exclusion criteria. Subsequently, power and energy logger was installed into the same buildings to monitor electricity consumption at specific intervals. For comparison, Building Energy Index (BEI) for each building was calculated. The study found that the building that scored higher in students’ performance, also has higher calculated BEI. As control for indoor comfort account for more than half of the total electricity consumption, the result suggested that electricity consumption influences students’ performance positively. The study also revealed that both buildings’ calculated BEI were lower than recommended by many standards. This suggests that these buildings, has extremely high potential of achieving green building status. If executed properly, the university campus, which equates a size of a small city, may achieve green campus status sooner than expected and may lead others in the flagship project towards a low-carbon university campus.